Apolipoprotein E genotype, gender and age modulate connectivity of the hippocampus in healthy adults. - Heise, V; Filippini, N; Trachtenberg, A; Suri, S; Ebmeier, K; Mackay, C (Academic Press Inc., 2014)
Important risk factors for Alzheimer's disease (AD) are ageing and the Apolipoprotein E (APOE) ε4 allele, with female APOE ε4 carriers having the greatest risk. In this study we investigated effects of AD risk factors on connectivity of the hippocampus, a structure that shows early AD related pathology. Resting-state functional magnetic resonance imaging and diffusion tensor imaging data from 86 cognitively healthy subjects aged 30 to 78years were analysed. Female APOE ε4 carriers showed overall significantly reduced functional connectivity between the hippocampus and precuneus/posterior cingulate cortex (PCC) and a significant age-related decrease in connectivity of these regions. In females and APOE ε4 carriers we found significantly reduced white matter integrity of the tract connecting the hippocampus and PCC with a significant positive correlation of white matter integrity and resting-state connectivity. Increased vulnerability of the connection between the hippocampus and PCC might be one reason for increased AD risk in female APOE ε4 carriers. Interventions targeting hippocampal connectivity might be especially effective in this at risk population.